Enhanced capacitance of composite TiO2 nanotube/boron-doped diamond electrodes studied by impedance spectroscopy. Issue 2 (21st November 2014) - Siuzdak, K.; Bogdanowicz, R.; Sawczak, M.; Sobaszek, M.
Abstract : We report on novel composite nanostructures based on boron-doped diamond thin films grown on top of TiO2 nanotubes. Abstract : We report on novel composite nanostructures based on boron-doped diamond thin films grown on top of TiO2 nanotubes. The nanostructures made of BDD-modified titania nanotubes showed an increase in activity and performance when used as electrodes in electrochemical environments. The BDD thin films (∼200–500 nm) were deposited using microwave plasma assisted chemical vapor deposition (MW PA CVD) onto anodically fabricated TiO2 nanotube arrays. The influence of boron-doping level, methane admixture and growth time on the performance of the Ti/TiO2 /BDD electrode was studied in detail. Scanning electron microscopy (SEM) was applied to investigate the surface morphology and grain size distribution. Moreover, the chemical composition of TiO2 /BDD electrodes was investigated by means of micro-Raman spectroscopy. The composite electrodes TiO2 /BDD are characterized by a significantly higher capacitive current compared to BDD films deposited directly onto a Ti substrate. The novel composite electrode of TiO2 nanotube arrays overgrown by boron-doped diamond (BDD) immersed in 0.1 M NaNO3 can deliver a specific capacitance of 2.10, 4.79, and 7.46 mF cm −2 at a scan rate of 10 mV s −1 for a [B]/[C] ratio of 2k, 5k and 10k, respectively. The substantial improvement of electrochemical performance and the excellent rate capability could be attributed to the synergistic effect of TiO2 treatment in CH4  : H2 plasma and the high electrical conductivity of BDD layers. The analysis of electrochemical impedance spectra using an electric equivalent circuit allowed us to determine the surface area on the basis of the value of constant phase element.